1982
DOI: 10.1007/bf00303006
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of ?Mediterranean type? glucose-6-phosphate dehydrogenase (G6PD) deficiency in Spain and description of two new variants associated with favism

Abstract: Glucose-6-phosphate dehydrogenase (G6PD); EC 1.1.1.49 from thirty-six unrelated Spanish males was partially purified from blood, and the variants were characterized biochemically and electrophoretically according to the methods recommended by the world Health Organization. Subjects were from multiple geographic regions within Spain, and all suffered from hemolytic anemia, either acute (34 cases) or chronic nonspherocytic (2 cases). Almost all the variants studied presented residual erythrocyte G6PD activity ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A comparison between the mutations in Arabs and Asians showed that most of the mutations responsible for the G6PDD shared among the two ethnic groups, which could be due to the long history of admixture among the two ethnic groups. These mutations were also shared with other ethnic groups, for example, the most frequent mutation among Arabs, p.S188F, was also frequently reported in Greece, southern Italy, Spain, Bulgaria, Romania, Turkey, and Israel14151617. We identified the most frequent mutations (p.S188F, p.V68M, p.I48T and p.N126D) and unique mutations (p.N135T, p.S179N, p.R246L, and p.Q307P) circulated among Arabs.…”
Section: Discussionmentioning
confidence: 95%
“…A comparison between the mutations in Arabs and Asians showed that most of the mutations responsible for the G6PDD shared among the two ethnic groups, which could be due to the long history of admixture among the two ethnic groups. These mutations were also shared with other ethnic groups, for example, the most frequent mutation among Arabs, p.S188F, was also frequently reported in Greece, southern Italy, Spain, Bulgaria, Romania, Turkey, and Israel14151617. We identified the most frequent mutations (p.S188F, p.V68M, p.I48T and p.N126D) and unique mutations (p.N135T, p.S179N, p.R246L, and p.Q307P) circulated among Arabs.…”
Section: Discussionmentioning
confidence: 95%
“…(14)], in a sample of G6PD Betica (not shown), which is the same as G6PD A-and is polymorphic in Spain (18), and in samples of G6PD A-from white men from Corsica and North Carolina (T.J.V. and L.L., unpublished), it seems reasonable to assume that it has spread to these places from Africa.…”
Section: Resultsmentioning
confidence: 89%
“…It is worth mentioning that in case 3 the diagnosis was established after an episode of acute haemolytic crisis due to fava bean ingestion. Favism, which is the most frequent clinical manifestation of glucose‐6‐phosphate dehydrogenase (G6PD) deficiency in Spain (Vives‐Corrons & Pujades, 1982), has also been described in GSH‐S deficiency by Oort et al (1961) and by Mohler et al (1970). Furthermore, the very low GSH content in these patients' RBCs may also explain the higher sensitivity of these cells to oxidative damage, as demonstrated by the increased production of MDA in presence of hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%